MANAJEMEN SUMBER DAYA MANUSIA (SDM) PAUD DI TK-AN-NUR KABUPATEN BUNGO - Eka Ristiani Fatimah (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2022)
Human resources are one of the important parts to be carried out in an organization or institution and company, because these human resources are included as the key or foundation for the success of an organization or institution. Human resources in PAUD institutions include principals and teachers and their staff, human resources in PAUD must be improved so that teachers can carry out their duties effectively and efficiently in achieving a goal. This research uses qualitative descriptive research, which describes the situation that occurs in An-Nur Kindergarten, Bungo Regency, data collection in this study is through direct observation and interviews with school principals and teachers. The number of teachers in An-Nur Kindergarten, Bungo district, is 10 teachers, 3 of them as assistant teachers, and 1 principal. The purpose of this study is to determine the management of PAUD human resources in An-Nur Kindergarten, Kedung Agung Village, Muko-muko Bathin VII District, Bungo Regency